2019
DOI: 10.1080/19476337.2018.1550442
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salt substitute containing KCl, L-histidine and L-lysine on the secondary structure and gel properties of myosin

Abstract: The effect of a salt substitute (SS) containing L-lysine (Lys) and L-histidine (His) on secondary structure and gel properties of myosin from grass carp was examined. The results indicated that the α-helix content of myosin treated with SS was 29.00%, 29.03% and 35.93% more than that with NaCl at 0.4, 0.6 and 0.8 mol/L (P < 0.05), respectively, suggesting that some fractions of the β-sheet, β-turn and random coil were transformed into α-helix. A similar pattern of storage modulus (G') was found between NaCl an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…For myofibrillar gel hardness, an obviously higher hardness induced by basic amino acids was obtained compared with 1% NaCl ( P < 0.05). These results were in accordance with previous studies, which pointed out that a higher α-helix structure and ΔG’ of the protein caused by basic amino acids had a positive role in stronger protein gel textural properties ( Lanier et al, 2005 ; Zhang et al, 2019 ). Nevertheless, what drew more of our attention was that the treatment time was different between the present study and the reported studies, that is, prerigor treating for the present and postrigor treating for the reported.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For myofibrillar gel hardness, an obviously higher hardness induced by basic amino acids was obtained compared with 1% NaCl ( P < 0.05). These results were in accordance with previous studies, which pointed out that a higher α-helix structure and ΔG’ of the protein caused by basic amino acids had a positive role in stronger protein gel textural properties ( Lanier et al, 2005 ; Zhang et al, 2019 ). Nevertheless, what drew more of our attention was that the treatment time was different between the present study and the reported studies, that is, prerigor treating for the present and postrigor treating for the reported.…”
Section: Resultssupporting
confidence: 93%
“…According to previous studies ( Zhang et al, 2017 , 2019 ), ΔG’ was employed in the present research to measure the G’ change rate. When the treatment time was 30 min postmortem, the ΔG’ of 1% NaCl + L-histidine, L-lysine and L-arginine was 22.63%, 11.75% and 2.29% greater than that of 1% NaCl, respectively ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%